Robsons Ten Group Classification of Cesarean Section at a Tertiary Center in Nepal - Baral, Gehanath; Shrestha, Alish; Sah, Arati; Gupta, Aswani Kumar (Journal of Nepal Health Research Council, 2021)
Background: Increasing trend in Ceasarean birth is the issue of both demand and supply side. One of the recommended tools to characterize every pregnancy admitted for childbirth is Robson ten-group classification system that may evaluate obstetric practice. The aim of the study was to assess the cesarean section pattern based on Robson’s classification in a central referral hospital. Methods: A retrospective census of childbirths at Paropakar Maternity and Women’s Hospital in Kathmandu performed from September 2018 to February 2019 based on obstetric record. Robson ten-group classification system was the research tool to collect data and Robson Classification Report Table was used to evaluate the data. Results: There were 10500 births with 34% (32-35%) overall cesarean section rate. Excluding spontaneous and induced labor the supposedly total prelabor CS is 14.5%. Group 1+2+3 size is 81% and 21% CS; 5+10 had 11.3% and 23.3% respectively. Prelabor CS (2b+4b) is 3.54% and additional 11% from malpresentation and preterm. Group CS rate from Class 5 onwards, and ratio of 1 and 2 are as recommended by Robson; 67% of CS were not picked up by Robson class due to indications evolved as the labor progresses and the attributes not pre-classified. Conclusions: The assessed quality of data and the type of obstetric population by Robson reference values prove this study as a representative research. But the indications of cesarean sections can be predicted for only one-third of pregnancy attributes classified by Robson class. To supplement this tool to reduce rising cesarean birth requires audit of indications at decision making level. Keywords: Cesarean section; indication; prediction; robson classification